Actividades físicas recreativas para mejorar la autoestima en las personas del Centro del Adulto Mayor “Los Arupos” del Municipio de Loja, ciudad de Loja 2024. - Chamorro Vicente, Nayely Soledad (2024)
The present curricular work was carried out with the objective of enhancing the self- esteem in people of “Los Arupos” Senior Center of the Municipality of Loja, in Loja city 2024. This research included a mixed approach of a descriptive and correlational type, with a quasi-experimental design. Some diagnostic instruments used for the object of study were applied to a sample of 8 older adults; for instance, an interview and the Rosenberg self-esteem test. Through the interview, it was possible to know and identify different aspects of social and familiar relationships, and the socio-emotional capabilities of the studied sample. Regarding the applied diagnostic test, it was evidenced that 11% of the population had low self-confidence, 56% had average self-esteem and 33% had high self-esteem. With the obtained results, a recreational physical intervention proposal was designed and implemented, which was structured in 10 workshops of activities to contribute to the self-esteem improvement. In addition, an instrument was executed to conclude the investigation, in which, an improvement in the mentioned topic was evidenced, showing an increase in the self-worth rating scale and observing a positive and meaningful change. This situation demonstrated effectiveness in the capabilities and skills of the group, notoriously boosting their self-appraisal and their motivation to carry out these activities. Keywords: Self-esteem, physical activities, recreational activities, older adult.